Population variation in fatty acid composition and response to climatic factors in Malania oleifera Chun et S.K. Lee - Hongguo Li; Ruizhen Wang; Zuwei Tian; Bingjiang Zhou; Runmei Duan; Ran He; Leiming Dong (BMC Plant Biology)
Abstract Malania oleifera Chun et S.K. Lee is a woody oil tree species and is rich in nervonic acid, which is associated with brain development. The variation in fatty acid composition and its response to environmental factors in natural populations has not been well studied. A total of 97 mature fruiting individuals were sampled from seven natural populations in Guangxi and Yunnan provinces, China. The fatty acid content (FAC) was 53.85%. Thirteen fatty acid components were identified. Nervonic acid (NVA), octadecenoic acid (OEA) and docosenoic acid (DSA) were the top three, averaging 45.68%, 30.21% and 14.03% of the FAC, respectively; the saturated fatty acid and unsaturated fatty acid contents were 4.82% and 95.18%, respectively. Coefficients of variation were low to moderate (7.64-18.42%) and Shannon-Wiener indices were moderate to high (1.80–2.04) for FAC, NVA, OEA and DSA. Significant variation between populations was observed for all traits, explaining 62.83%, 40.54%, 21.98% and 32.85% of the variance for FAC, NVA, OEA and DSA, respectively. The strong collinearity among traits summarized them into three principal components. FAC was positively correlated with NVA and NVA was negatively correlated with OEA and DSA at both the population and phenotypic levels. This pattern was significantly divergent from those documented in tree species with low NVA yields. The production of FAC and NVA is facilitated by elevated temperatures and reduced relative humidity. These findings provide a foundation for genetic improvement, industrial exploitation, resource management, and sustainable development of this species.